The Relationship between Vocabulary Knowledge and Reading Comprehension Ability of Junior High School Students - Andi Fitri Rahmasari M; Sultan Baa; Chairil Anwar Korompot (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This research aimed to discover the relationship between students' vocabulary knowledge and their ability to comprehend text. The researchers in this study employed a quantitative approach. Students from SMPN 1 Liliriaja's ninth-grade class participated in this study. Purposive sampling was used to collect the data. The correlation between the two variables was determined by comparing the obtained data. Students' vocabulary mastery and reading comprehension were found to have a strong correlation. The possibility of the correlation value. (2-tailed) becoming 0.000, which is below the significance level, can be verified (0.05). As a result, the researchers can rule out the null hypothesis (H0) and accept the alternative hypothesis (Ha). Because the value is 0.698, it can be concluded that students' vocabulary knowledge and reading comprehension have a significantly strong correlation (0,61-0,80).